Coupling patterns between para‐glacial and permafrost degradation responses in Antarctica. Issue 9 (24th February 2015) - Oliva, Marc; Ruiz‐Fernández, Jesús
ABSTRACT The recently deglaciated environments in maritime permafrost regions are usually affected by very active paraglacial processes. Elephant Point is an ice‐free area of 1.16 km2 located in the SW of Livingston island (South Shetland Islands, Antarctica). Between 1956–2010 the retreat of the ice cap covering most part of this island has exposed 17.3% of the land surface in this peninsula. Two geomorphological units were identified in this new ice‐free area: a moraine extending from the western to the eastern coastlines and a relatively flat proglacial surface. The glacier in 1956 sat in contact with the northern slope of the moraine, but its accelerated retreat ‐ in parallel to the warming trend recorded in the Antarctic Peninsula ‐ left these areas free of glacier ice. Subsequently, the postglacial evolution was controlled by the relaxation phase typical of paraglacial systems. The typology and intensity of geomorphological processes show a significantly different dynamics between the southern and northern slopes of the moraine. This pattern is related to the different stage of paraglacial adjustment in both slopes. In the southern side, on coarser sediments, pronival ramparts, debris flows and alluvial fans are distributed, with a low to moderate activity of slope processes. In the northern side, mass wasting processes are extremely active on fine‐grained unconsolidated sediments. Ice‐rich permafrost is being degraded by thermokarst processes. Landslides and mudflows transfer large amounts of sediments down‐slope. The surface affected by retrogressive‐thaw slumps in the moraine has been quantified in 24, 172 m2, which accounts for 9.6% of its surface. The abundance of kettle‐lakes is also indicative of the degradation of the ground ice. Paraglacial processes are expected to continue in the moraine and proglacial area in the near future, although their intensity and duration will depend on the magnitude and rate of future climate trends in the northern Antarctic Peninsula. Copyright © 2015 John Wiley & Sons, Ltd.